Student outcomes and learning environments at the tertiary level in New Zealand: the develpment of an assessment framework - Hewison, Donald Edward (Curtin University, 2007)
This thesis reports the findings of a case study into the outcomes and learning environments of students studying for a Diploma of Technology at a New Zealand Tertiary Education Institution. The primary focus of the study was to develop an assessment framework that would facilitate simultaneous assessment of the local Institute achievement-based Diploma of Technology and the competency-based assessment of a National Diploma that the local diploma subsumed. From this primary focus on assessment, the study provided the opportunity to undertake a grounded theory study of literature that impacted on the learning environment, supported the necessity to rationalise the student learning outcomes from both an academic and work skill perspective, and presented a suitable situation in which to take a fresh look at the method of grading and marking students’ assessment material.The grounded theory study grew out of the need to condense the vast amount of literature that was gathered in the process of searching for background material to use in the building of a foundation on which to construct a dual assessment model. Although no literature was found that specifically dealt with the simultaneous dual assessment, a large amount of material was found that related to various aspects of the learning environment. Through the process of a grounded theory study, this material was condensed into categories of data that in turn were used to develop a theoretical model of an ‘ideal’ learning environment. Into this model was also added the results of a questionnaire based research study into the perceived need for diploma graduates to have a range of employability skills. This study involved a range of employers who considered themselves likely to employ a diploma graduate. Because the learning outcomes for the two diplomas covered essentially the same material yet the actual wording of the outcomes were substantially quite different, there was a need to rationalise the sets of learning outcomes for each diploma. This process led to a common set of outcomes that in turn were used as a focus for students’ learning and assessment.Once these common outcomes had been identified, a rubric based marking/scoring system was developed so that both students and teacher could quickly grade students’ assessment material and then convert that grade into a mark. The use of the grade facilitated the assessment of achievement against a unit standard and the resultant marks satisfied the need for an achievement mark. The results and findings from the various studies were then translated into a working model that was used for two courses over one semester. Various other research methodologies were then used in order to provide some evaluation of the working model.The thesis does present some of the difficulties facing tertiary teachers in an environment that is becoming more and more of a production line business rather than a service to provide learning opportunities for students. However it also presents solid evidence that teachers can take measures to prove themselves through study and initiative and provide those focussed learning environments where students can attain the outcomes necessary for a successful career in tomorrow’s world.